The Studying of the Relationship between Organizational Silence and Job Burnout and Its Consequences - Jahez, Wajiha; Aadel, Enjila (Journal of Social Sciences - Kabul University, 2023)
Human power is considered as the most valuable organizational capital. According to the new organizational structures, their human resources have been affected by various threats, among which the phenomenon of "job burnout" and "organizational silence" can be mentioned, when human power as the most important organizational capital feels job burnout and remains silent, the leadership of the organization must feel a great danger in front of him. The purpose of this research is to identify the relationship between job burnout and organizational silence and their consequences. This research has been written using scientific articles published in scientific journals and authoritative books. The findings of this research showed that there is a relationship between organizational silence and job burnout. In fact, job burnout causes organizational silence and thereby causes a decrease in motivation, absenteeism, leaving the job, and as a result, decreases the effective performance of employees and the organization.